Batak Toba Script, Preserving Its Authenticity in Globalization Stream - Lubis, Donal Fernado; Bowo, Tri Arie (Nusantara Science and Technology Proceedings)
This paper exposes the existence of Batak Toba's ancient script and the shift of its authenticity values during the rapid development of technology. The analysis adapts cultural and historical approaches to be exposed qualitatively by observing several transcripts virtually. Technology is viewed from two perspectives: a media that brings this ancient heritage back to be part of modern culture; and the means that lead this ancient writing to lose its authenticity. Several former documents from field and library research are compared, especially the use of several computer software, which has been developed to enable users to write in Batak Toba script through transliteration. The result reveals that efforts to conserve this cultural heritage should be accompanied by careful linguistic assistance so that the script and its writing convention would be maintained.